A Bit of History of Russophilism and Rusofobstvo in Bulgaria - Kosik Viktor (Вестник Православного Свято-Тихоновского гуманитарного университета: Серия ИИ. История, история Русской Православной Церкви)
The text of the article is associated with well-known in the history of the phenomena of russophilism a and rusofobstvo in Bulgaria in the nineteenth century. For complex historical background, rich in political surprises, these two opposite phenomena represented in the sayings and poems of the representatives of the Bulgarian national-minded intellectuals — him P., Rakowski, Z. Stoyanov, L. Karavelov, I. Vazov. Some of them were afraid of turning Bulgaria into a Russian province, others saw in the mighty Orthodox and Slavic Russia salvation of his homeland, his people. Still others saw the future of their country in Alliance with the Ottoman Empire and the creation of a dual Turkish-Bulgarian monarchy. Was observed and the change in its position as L. Karavelov underlining in his lines fortress of the Russian-Bulgarian friendship. Marked and attitude of Russian thought through reﬂections of a Russian diplomat, philosof, and publicist Konstantin Nikolaevich Leontiev to Bulgaria, the Russian-Bulgarian relations, which seemed to him not unlike many of his contemporaries, rainbow. Considerable attention is paid to the «troubled» by many parameters time when, after the Russo-Turkish war of 1877–1878 signiﬁ cant part of the Bulgarian lands had the opportunity to form their own state in the form of a de facto independent from the Ottoman Empire Bulgarian principalities, in which the processes of russophilism and rusofobstvo not only not subsided, but has been further aggravation, especially after accomplished without the knowledge of Russia, the uniﬁcation of Principality of Bulgaria with southern Bulgaria, not having statehood. In conclusion, given a brief description of russophilism and rusofobstvo.